Development and Validation of the Multiculturally Responsive Teaching (MRT) Instrument: A Rasch Model Analysis for Assessing Multicultural Competence in English Education - Thresia, Fenny; Raja, Patuan; Nurweni, Ari; Kadaryanto, Budi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to develop and validate the Multiculturally Responsive Teaching (MRT) Instrument to assess the multicultural competence of pre-service English teachers. Multicultural competence is essential in fostering inclusive learning environments, yet there is a lack of standardized instruments tailored to measure this construct effectively within teacher education. The study employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The instrument was designed based on key dimensions of multicultural competence: racism, social class, religious diversity, gender inequality, language diversity, and cultural differences aspects. Data were collected from 335 English Education students across Indonesia, and analyzed using the Rasch Model to assess the instrument's validity and reliability. Findings indicate that the MRT instrument demonstrates high internal consistency, with a Cronbach’s Alpha of 0.92, a person reliability score of 10.14, and an item reliability score of 5.14, suggesting strong measurement precision. The Person-Item Map (Wright Map) confirms the instrument's ability to differentiate respondents' competence levels, while the rating scale analysis supports the functionality of the Likert scale categories. The classification of item difficulty based on Logit Value Index (LVI) reveals a well-structured hierarchy, ensuring appropriate item calibration. The study concludes that the MRT instrument is a valid and reliable tool for measuring multicultural competence among preservice English teachers. Its application can support curriculum enhancement, professional development, and policy formulation in teacher education programs. Future research is encouraged to expand its implementation in different educational contexts to further validate its effectiveness.